Spain : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper describes economic developments in Spain during the 1990s. Spain emerged from a recession in 1994, as real GDP increased by 2 percent, following a decline of 1.1 percent in 1993. The recovery was triggered by a surge in exports that started in mid-1993, in turn spurred by the sharp depreciation of the peseta in 1992-93, and the incipient recovery of domestic demand in other European countries. Private consumption picked up in early 1994 but provided only a moderate contribution to the turnaround.